Business Process Reengineering of Sustainable Teak Forest at Agroforestry Industry - Alkaff, Muhammad; Marimin, Marimin; Arkeman, Yandra; Sukardi, Sukardi; Purnomo, Herry (Universitas Prasetiya Mulya, 2016)
Forest destruction both in the form of deforestation and degradation continues. Forest management on the basis of partnership with the community is also one of forest management methods to tackle deforestation. Agroforestry company has a commitment to support legal teak supplies and support teak forest afforestation. Plant breeding efforts were being undertaken all national agroforestry company and implemented in cooperation with BPPT as a partner to obtain superiorteak plants. A problem in producing a superior teak seedling is the high cost of seed production. Because of this, teak seedlings produced. Materials used for the study were obtained from questionnaires carried out by employees. The data were analyzed using descriptive analysis, structured equation model and value stream analysis tools. The results reveal that the main factors affecting the production process of teak seedlings are transportation, process, human, material and machine. The improvement of production system teak seedlings will be applied in the following order of priority: transportation with 60.8% influential level, motion with 49.5% effective level, defect with 3.8% influential level, and inventory with 2.5% influential level.